(untitled) (Eurasian Scientific Herald, 2025)
The article discusses the main qualities of a creative teacher in the process of training pedagogical personnel, methods for developing creativity, the importance of using this process in pedagogical education, and recommendations for forming the creative potential required of a modern teacher